Aplikasi Penanganan Masalah Laboratorium dan Kelas pada Sistem Pembelajaran Perguruan Tinggi - Fredy Susanto; Ari Asmawati (Teknik Informatika, 2019)
Maintenance of laboratory computers is a dilemma for some laboratory staff, because damage to peripherals in the lab can be alternated. So with this we made a lab monitoring system that uses thin client technology. Moreover, the use of lab facilities is quite large so that computer users who do not have enough time to handle hardware damage, which results in many computers being damaged. Therefore the implementation of a damage monitoring or monitoring system on a Lab computer was made to help monitor computer users in detecting damage to computer hardware along with solutions to deal with damage. With problems with damage to the computer lab. The current system still uses a manual inspection system using a media laboratory computer damage checklist. Therefore, in improving maintenance services in the Lab, an application system must be developed that supports the accuracy and accuracy of the maintenance laboratory so that it can assist technicians in monitoring the lab, both software and hardware. The damage is minimized with the help of thin client technology.